Methods of determining indicators of similarity of 3D motion - Flisiak, Piotr; Kuszyk, Marcin (Journal of Computer Sciences Institute, 2020)
This paper includes methods for comparing three-dimensional movements with data saved in a C3D file usingPearson’s linear correlation algorithms and a mean-quadratic error. Their accuracy was also examined. The movements of a person rowing on an ergometer at a distance of 500 meters were recorded by motion acquisition technology. The article presents the created application used for analysis.